Low-cost synthetic model for training and simulation of nipple-areola complex (NAC) reconstruction - Pedro Lucena de Aquino; Arthur Antunes Coimbra Pinheiro Pacífico; Letícia Fontenelle Fernandes; Giselle Ferreira de Souza; Sarah Gurgel Ponte Fontenelle; Ana Heloísa Feitosa de Macêdo Pereira; Pâmella Christine de Souza Munhoz; Letícia Castelo Branco de Oliveira (Revista Brasileira de Cirurgia Plástica)
Introduction: Reconstruction of the nipple-areola complex (NAC) is indicated when this member is amputated in mastectomies to ensure a more natural appearance to the reconstructed breast. It was first reported by Berson in 1946, but there are currently more than 60 different techniques, all described in the last 8 decades. Method: To construct the models, a female bust mannequin, foam sheet, mesh, scissors, Styrofoam glue, and sewing material were required. Once completed, the flap could be marked with a fine-needle brush, and the various techniques described in the literature could be practiced. The model was presented to the plastic surgeon supervising the Plastic Surgery League of the University of Fortaleza and was approved and recommended for low-cost simulation. Results: The interest of students in a theoretical class on NAC reconstruction techniques sparked interest in producing a synthetic training model, and due to its ease of practical handling and complete simulation, it was decided to use synthetic material, which allows training in the CV Flap technique. Conclusion: The synthetic model for the reconstruction of the nipple-areola complex can accurately simulate the steps of the real surgical procedure, in addition to providing benefits such as good accessibility and low production cost.